Development of sustained-release floating tablets of diltiazem hydrochloride - Hung Pham Van; Tung Nguyen Thanh; Nhat Hoang Thi Anh; Hieu Bui Trung; Uyen Dinh Thi Thu; Duyen Nguyen Thi Thanh (Vietnam Journal of Science, Technology and Engineering, 2025)
Diltiazem hydrochloride (DTZ), utilised for cardiovascular conditions, possesses a short half-life, necessitating frequent dosing. To enhance compliance, sustainedrelease (SR) floating tablets were developed using a Quality by Design (QbD) approach. This study aimed to formulate DTZ 120 mg tablets, conforming to United States Pharmacopeia 2023 dissolution standards, at a batch size of 1000 tablets. Wet granulation was employed with hydrophilic polymers to control drug release, while gas-generating excipients were used to ensure buoyancy. Tablets were evaluated for floating characteristics, in vitro dissolution, and drug release mechanisms. Hydroxypropyl methylcellulose K100M controlled release (HPMC K100M CR), NaHCO3, and PVP K30 significantly influenced output variables and were selected for the experimental design. The release rate of DTZ decreased with higher amounts of HPMC and NaHCO3, while PVP had a minimal effect. The optimised formula included HPMC K100M CR (501.5 mg), NaHCO3 (244.8 mg), PVP K30 (32.4 mg), and other excipients. Tablets exhibited a floating lag time of less than 1 minute and a floating duration exceeding 30 hours. Dissolution results met United States Pharmacopeia standards, showing values of 26.99±0.97% at 6 hours, 50.31±0.40% at 12 hours, and 91.46±1.92% at 30 hours. The manufacturing process for 1000 tablets per batch was established, and process parameters were investigated.